Analisis Solvabilitas Terhadap Kinerja Keuangan Pada Seabank Tahun 2022-2024 - Xenia Irene Sandy Landjang; Yuni Riskita Mangopo; Indra Eka Wardana Toii (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to analyze the financial performance of Seabank Indonesia, the leading digital bank in Indonesia (Databooks, 2025), through solvency ratios, namely Capital Adequacy Ratio (CAR), Debt to Assets Ratio (DAR), and Debt to Equity Ratio (DER) during the period of 2022-2024. Secondary data from financial reports were processed using a quantitative descriptive approach, supported by trend analysis and comparative analysis to assess Seabank’s financial performance. The results indicate a declining trend in CAR from 39.67% to 30.80%, indicating a reduced ability to bear risks. Meanwhile, DAR and DER significantly increased in 2024, reflecting a high reliance on debt financing and an unbalanced capital structure. This condition raises financial risk and demands strategies for capital strengthening and stricter debt control. The study recommends that Seabank evaluate capital strategies, control debt growth, strengthen equity, and implement effective risk management to maintain long-term financial stability.